2018
DOI: 10.1155/2018/1810846
|View full text |Cite
|
Sign up to set email alerts
|

Icariin-Loaded TiO2 Nanotubes for Regulation of the Bioactivity of Bone Marrow Cells

Abstract: To explore the effects of icariin on the biocompatibility of dental implants, icariin-(ICA-) loaded TiO 2 nanotubes were fabricated on Ti substrates via anodic oxidation and physical absorption. The surface characteristics of the specimens were monitored by field emission scanning electron microscopy (FE-SEM), X-ray diffractometry (XRD), contact angle measurements (CA), and highpressure liquid chromatography. Additionally, the activities of bone marrow cells, such as cytoskeletal, proliferative activities, min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Rupp et al [ 68 ] demonstrated that the wettability of various Ti surfaces could be greatly influenced by its roughness and morphology, while Takebe et al [ 69 ] highlighted that the hydrophilic character of TNT structures could be slightly increased due to the easy infiltration of water into the TiO 2 porous network, causing a decrease of contact angle value. In our study, the contact angles of the bare TNT and Ica-loaded substrates were significantly lower in comparison to that of flat Ti, in compliance with previously reported data [ 43 ]. As a means to load the biologically active molecules and drugs onto the surface of implants, the physical adsorption method has been widely applied in previous studies [ 40 , 70 , 71 ], due to its main advantage of ensuring the chemical structure and biological characteristics of the loaded molecules [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Rupp et al [ 68 ] demonstrated that the wettability of various Ti surfaces could be greatly influenced by its roughness and morphology, while Takebe et al [ 69 ] highlighted that the hydrophilic character of TNT structures could be slightly increased due to the easy infiltration of water into the TiO 2 porous network, causing a decrease of contact angle value. In our study, the contact angles of the bare TNT and Ica-loaded substrates were significantly lower in comparison to that of flat Ti, in compliance with previously reported data [ 43 ]. As a means to load the biologically active molecules and drugs onto the surface of implants, the physical adsorption method has been widely applied in previous studies [ 40 , 70 , 71 ], due to its main advantage of ensuring the chemical structure and biological characteristics of the loaded molecules [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the contact angles of the bare TNT and Ica-loaded substrates were significantly lower in comparison to that of flat Ti, in compliance with previously reported data [ 43 ]. As a means to load the biologically active molecules and drugs onto the surface of implants, the physical adsorption method has been widely applied in previous studies [ 40 , 70 , 71 ], due to its main advantage of ensuring the chemical structure and biological characteristics of the loaded molecules [ 43 ]. Our results indicate that Ica was released from the TNT-DP substrate in a sustained manner, therefore indicating that Ica was loaded successfully onto the TNT-DP surface and that its biological activity was preserved.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The experimental results in vitro and in vivo showed better bone responses when compared to smooth surfaces without nanotubes, suggesting the significance of having specific sites for maintaining the compounds on the surface [ 37 ]. Icariin (ICA) was shown to be a promising osteoinductive compound for bone regeneration studies; some authors reported the application of ICA by simple physical absorption into TiO 2 nanotube surfaces [ 38 ]. Releasing ICA improved the spreading, mineralization and expression of some bone-associated markers of bone marrow cells, suggesting a promising option for new implant surfaces [ 38 ].…”
Section: Methods To Develop Bddss For Oral Bone- and Periodontal-rela...mentioning
confidence: 99%
“…Icariin (ICA) was shown to be a promising osteoinductive compound for bone regeneration studies; some authors reported the application of ICA by simple physical absorption into TiO 2 nanotube surfaces [ 38 ]. Releasing ICA improved the spreading, mineralization and expression of some bone-associated markers of bone marrow cells, suggesting a promising option for new implant surfaces [ 38 ].…”
Section: Methods To Develop Bddss For Oral Bone- and Periodontal-rela...mentioning
confidence: 99%